Epitaxial growth of the intermetallic compound NiAl on low-index Ni surfaces in Ni/Al reactive multilayer nanofoils. (15th April 2018) - Baras, F.; Politano, O.
Abstract: Crystal growth in the case of self-propagating reactions in Ni-Al nanofoils was investigated by means of molecular dynamics simulations. We studied the heteroepitaxial growth of NiAl on Ni during mixing and alloying at interfaces. Three low-index Ni surfaces were considered. In the case of the (001) and (111) orientations of Ni, a layer-by-layer formation occurred. Four orientations of NiAl grains were observed in (001) and six in (101). The orientation relationships of NiAl(101) with Ni(001) and with Ni(111) were derived. For the (101) orientation of Ni, massive crystallization was observed in the form of grains tilted in relation to the interface. The microstructure evolution was tracked along with grain orientation dynamics. In all cases, a simple geometric construction based on the relationship between unit cells of Ni and NiAl explains crystal growth specificities. The nucleation process and growth kinetics were also investigated. The present study proves that crystal growth varies considerably, in relation to Ni orientation. Graphical abstract: Image 1